Review: Global perspectives on teaching excellence – A new era for higher education - Käck, Annika (Högre utbildning, 2018)
Are you searching for a book that discusses teaching excellence from both a global and future perspective? In that case, Global perspectives on teaching excellence - A new era for higher education is a highly relevant and interesting book with contributions from 42 individuals, all involved in higher education in many countries. Christine Broughan, Graham Steventon and Lynn Clouder, researchers from Coventry University in the United Kingdom, are the editors. In this book, the concept of teaching excellence is explored by international authors who highlight a number of key issues. One issue is that teaching excellence has no international definition because it is such a complex subject covering diverse ontological, epistemological and cultural contexts. We can read this book with three questions in mind: If and how teaching excellence can be measured; what impact frameworks, initiatives and awards have on teaching excellence; and, what are the new challenges for global teaching excellence in the 21st century? The authors’ focus is a blend of political, theoretical and applied research which gives the reader many different perspectives on teaching excellence.